Irisin, A Fascinating and Multifunctional Protein: Implication for Health - Defi, Irma Ruslina; Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Fibronectin type III domain-containing protein 5 (FNDC5), or also known as irisin, has been identified for two decades but almost completely disregarded for 10 years. It is present in skeletal muscle, heart, and brain, and in reaction to exercise can transform white adipose tissue into brown. Since then, irisin has gained a lot of attention for its potencies in treating metabolic disorders. In this review article, the potential future of irisin especially on metabolism and aging process will be discussed.CONTENT: Sedentary lifestyle is acknowledged as risk factor for type 2 diabetes mellitus, obesity, immune system issues, asthma, and neurological or heart illness. Irisin is secreted by muscle cells when exercising, produced after the proteolytic cleavage of FNDC5 protein. Irisin has positive impacts on maintaining physiological balance including reducing inflammation, keeping the bone homeostasis, as well as influencing metabolic processes and the neurological system function. Due to these many and advantageous characteristics, irisin could be a possible choice for preventing and managing disorders associated with modern society, and finding the agents to increase irisin can be beneficial.SUMMARY: Irisin offers a fresh potential basis for kinesitherapy and shows promise as a therapeutic target due to its various biological activities. Irisin pathway can be activated through dietary changes, the use of natural substances and drugs and can interact with this signalling pathway which involved peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and uncoupling protein mRNA 1 (UCP1) to resolve obesity and its metabolic comorbidities.KEYWORDS: irisin, FNDC5, exercise, inflammation, obesity, nervous system